Impact of depression, anxiety, and COVID-19 diagnosis on social isolation trajectories during the pandemic: A 3-year prospective cohort study - Juhee Choi; Gaeun Son; Ye-Seul Kim; Kee-Hong Choi; Jungeun Kim; Subin Park (PLoS ONE, 2025)
Background The coronavirus disease 2019 (COVID-19) pandemic has profoundly affected physical and mental health. Since the onset of the pandemic, the prevalence of depression and anxiety has significantly increased. Quarantine and social distancing, implemented to control the spread of COVID-19, have exacerbated social isolation. This study aimed to longitudinally examine how the severity of depression and anxiety, along with COVID-19 diagnosis, influenced the trajectory of social isolation throughout the pandemic. Method This longitudinal study collected data from South Korea in three waves: 2021, 2022, and 2023. The final sample included 2,395 participants (mean age = 46.32, SD = 16.47) who completed a face-to-face interview survey. Depressive symptoms were measured using the Patient Health Questionnaire-9, while anxiety was assessed using the Generalized Anxiety Disorder-7. Social isolation was evaluated using the Loneliness and Social Isolation Scale. The data were analyzed using multilevel modeling with a three-way interaction design. Results A significant three-way interaction was found between time, depression severity, and COVID-19 diagnosis, while anxiety severity showed no significant interaction. Among the participants diagnosed with COVID-19, those with severe depressive symptoms exhibited an increase in social isolation over time. The positive effect of time was strengthened when the depression severity was severe, whereas it was weakened in participants with moderate or mild depressive symptoms. For participants without a COVID-19 diagnosis, social isolation tended to decrease over time across all levels of depressive symptoms, excluding cases with no depressive symptoms. Conclusions The three-way interaction results indicated that the severity of depressive symptoms and COVID-19 diagnosis status significantly influenced social isolation trajectory over time. Individuals diagnosed with COVID-19, particularly those experiencing severe depression, have an increased risk of worsening social isolation over time. This underscores the need for intensive and sustained psychological support and intervention for vulnerable individuals.